2018
DOI: 10.17583/rise.2018.3547
|View full text |Cite
|
Sign up to set email alerts
|

Bullying. Description of the roles of victim, bully, peer group, school, family and society.

Abstract: This research defines, through an extensive literature review, the roles played by the victim, bully, peer group, school, family and society in the dynamics of bullying. Finally, we conclude that the complexity and diversity of the actors should lead us to rethink the traditional definitions of school bullying, to stake out the focus of research projects and to reconstruct prevention and action policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
10
0
4
Order By: Relevance
“…It has also been found that friendship quality is associated with prosocial behavior towards friends [11], prosocial behavior being essential in promoting a positive school climate, and with better adjustment for early adolescents [12]. Importantly, peer relationships based on friendship act as a protective factor against bullying [13,14]. Badhwar [15] conceptualized friendship as characterized by "mutual and reciprocal goodwill, trust, respect, affection, and pleasure ( .…”
Section: Fostering Supportive and Safe Educational Environmentsmentioning
confidence: 99%
“…It has also been found that friendship quality is associated with prosocial behavior towards friends [11], prosocial behavior being essential in promoting a positive school climate, and with better adjustment for early adolescents [12]. Importantly, peer relationships based on friendship act as a protective factor against bullying [13,14]. Badhwar [15] conceptualized friendship as characterized by "mutual and reciprocal goodwill, trust, respect, affection, and pleasure ( .…”
Section: Fostering Supportive and Safe Educational Environmentsmentioning
confidence: 99%
“…This is in keeping with findings reported by Andrés and Barrios (2009) [36], who have stated that it is necessary to strengthen coexistence in the school environment. Along the same lines, Acosta et al (2018) [37] have demonstrated that there are four elements that require attention when analyzing the school climate: attachment relationships, assertiveness, empathy, and integration of the individual in the school. Integration of the individual is one of the aspects most highlighted by the academic literature, being examined in studies such as those developed by Cava (2011) and Andrés and Barrios (2009) [35,36].…”
Section: Discussionmentioning
confidence: 95%
“…School bullying is a problem that is seen in any school context and brings with it serious consequences making it essential to conduct research on the factors that may assist in stopping it [31,32]. In the school investigated, school bullying had a reported prevalence of 21%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the prevalence of cyberbullying among minors indicate an urgent need for scientific evidence regarding how to prevent such bullying as early as possible [1,2,3], particularly in primary and secondary school. There is abundant scientific literature [4,5,6] that describes how cyberbullying affects young people in different countries.…”
Section: Introductionmentioning
confidence: 99%